El sujeto humano como objeto de la Psicología: las funciones psíquicas en Max Scheler y en Carl Stumpf - Sánchez-migallón, Sergio (Revista de Filosofía, 2006)
Max Scheler defends that the ultimate subject of human acts is different from the “I” often worked upon in Psychology. To show it he distinguishes “acts”, which correspond to the “person”, from “functions”, which correspond to the “I”. In that exposition, developed in his Ethics, he makes reference to an essay by Carl Stumpf about the “psychic functions”. In this paper that same essay is analised and the significance that Scheler gives to it is evaluated